A implantação do Ensino Fundamental de Nove Anos no Estado do Paraná - Oliveira, Delvana Lucia de (2009)
The aim of the research was to analyze the process of implementation of the Fundamental Teaching of Nine Years in Paraná State. The methodological procedure of data collection of the empirical material and the research analysis is according to the qualitative approach. The analysis was based upon two axis: a) the legal documents of the enlargement process of the Fundamental Teaching of Nine Years, such as the Federal Constitution of 1988, the National Education Plan, law nr. 10.172/01, The Diretrizes e Bases da Educação Nacional, law nr. 9.394/96, Opinion Reports and the Resolution of the National Council of Education, law nr.11.114/05 and the law nr. 11.274/06 of the National Congress , Opinion reports and Deliberations of the National Council of Education; b) the content of the interviews with the politic and administrative subjects who directly participate in the legal decisions of the implementation of the Fundamental Teaching of Nine Years in Paraná State. The theoretical referential was based on critical authors who study the concepts of State and civil society such as: Bobbio (1982, 2004) and Nogueira (2005); the implementation of public politics was concentrated on the studies of Azevedo (2001), Fávero (2001) and Saviani (1997, 1999, 2002, 2007), as well as on those who work with the obligatory education, such as: Carvalho (2004), Cury (2002, 2005), Sacristan (2001), among others. The research obtained such results: a) The Opinion reports own their legality because the obligatory in our teaching system is based on the emission of the documents by the councils followed by the civil society; b) about the administrative aspect we have to consider, from the interviewers reports, that the infrastructure issues were understood as barriers for the Fundamental Teaching of Nine Years implementation. Thus, we emphasize that such context is connected to a lack of consideration of what was settled in the previous documents before this implementation, the National Education Plan, that since 2001 establishes the enlargement of the Fundamental Teaching from eight to nine years; c) although the Federal Constitution of 1988 reassures the Fundamental Teaching as a subjective public right, that requires from the Public Power favorable conditions so that the right can be accomplished. The debate about such issue did not show some concerning with this legal instrument which demands more commitment from the administrators’ actions for the educational area; d) the presence of a conception of education, which is attached with the maturity issue, when some defended the introduction of the six-year-old child in the first year, because they believe in such age she/he would be more prepared to be enrolled into the Fundamental Teaching level of education.